A prospective study of acceptability, safety and demographic profile for post placental intrauterine contraceptive device - Jain, Neha; Choudhari, Hemangi K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to study the acceptance rate, safety, demographic profile and complication of post placental intrauterine contraceptive device (PPIUCD). Methods: Study was prospective, interventional study, held in department of Obstetrics and Gynaecology at authors tertiary care centre. Number of participants was 280. Counselling about family planning was done in antenatal OPD and indoor ward. Total duration of study was 18 months. Selection of participants done based on selection criteria. Participants who accepted postplacental intrauterine contraceptive device as method of contraception followed up to 6 weeks postnatal for complication related to PPIUCD. Results: Authors noted that acceptance rate of PPIUCD was 13.6% and main reason for acceptance was its long acting reversible nature and main reason for denial was ‘do not want contraception immediately’. In present study there was statistically significant association between parity and birth order. However, literacy, urban locality and employment had positive influence over acceptance. If good technique of insertion will be used than expulsion rate will also reduce as seen in present study i.e. expulsion rate only 2.6 %. Conclusions: Post placental intrauterine contraceptive device is one of the best long acting reversible contraceptive methods. It does not affect breast milk production. Woman does not need extra visit to clinic for contraception and she is ensured that she has adequate contraception before getting discharge from hospital. PPIUCD provide adequate birth spacing between two children which reduces maternal and child morbidity.